Reward structures and negotiation strategies: The use of deception in negotiation - LIM, Jermaine Pin Xiu (Institutional Knowledge at Singapore Management University, 2021)
This present study investigated the effect of outcome interdependence on different types of deceptions – mutually beneficial and self-interested deception, in a negotiation context. 150 SMU students were recruited to engage in a negotiation task and were randomly assigned to either a high outcome interdependence condition where the monetary reward was awarded based on the points scored by the dyad or a low outcome interdependence condition where the monetary reward was awarded based on the points scored by the individual. The results showed that in a self-rated scale, dyads in the low outcome interdependence condition rated themselves to have engaged in more mutually beneficial and self-interested deception compared to dyads in the high outcome interdependence condition. Similarly, when two blind raters were asked to code the chat for deception, they found that dyads in the low outcome interdependence engaged in more mutually beneficial and self-interested deception, though the former was not statistically significant. Further research is required to examine if outcome interdependence could potentially have a similar effect on other types of deception (e.g. emotional deception) or if the effects would hold across different mediums (e.g. face-to-face vs online).